Households; dependence of GDP "spending growth in the last decade of Colombian" (2013)
Over the last decade have emerged different analysis of the behavior of economic growth in Colombia, different to the relationship between inflation and household spending, so that the next document provides a theoretical analysis and graph of the effect of price level on the proportion of household spending in the final calculation of GDP in the period between 2000 and 2010, justifying the expenditure because of damage to the structure of allocation of revenue and also with the level of wages in the economy. In the end, is criticized law enforcement with respect to the primary function of the Bank of the Republic in relation to the control of the price level of the economy and examines the consequences of the international economic crisis on the distribution of household income Colombians